INDEKS PEMBANGUNAN MANUSIA DALAM ISLAM - Inayah Swasti Ratih; Tamimah (IZZI: Jurnal Ekonomi Islam, 2021)
The purpose of this research is to explain the concepts and indicators of IslamicHuman Development. This research method uses descriptive qualitative research, thedata source used is secondary data. The result of this research is the concept of IslamicDevelopment Economics not only for the benefit in the world, but also benefit of thehereafter so that benefit is the main thing that must be met. The fulfillment of benefitin the Islamic Development Economy is based on the indicators contained inMaqashid Syariah.